Application of Team Coaching Tools for University Education – Case Study - Popovics, Péter; Gál, Tímea; Katonáné, Judit; Árváné Ványai, Georgina (International Journal of Engineering and Management Sciences, 2017)
In 2010 the innovative Finnish higher education system (Tiimiakatemia – Team Academy) was launched at University of Debrecen Faculty of Economics and Business, which was also awarded by OECD and has been run at JAMK University of Applied Sciences in Jyvaskyla since 1993. In this system, we create team entrepreneurs who have to work together in teams. In this research the authors would like to look at how we can use the team coaching tools as a part of this model in our team entrepreneur education system to build high performing teams. Tuckman named five stages of team formation: forming, storming, norming, performing and adjourning. A new team cannot be expected to perform as an excellent team when it first comes together. It takes time forming a team, and they often go through recognizable stages as they change  from being a collection of strangers to a united group with common goals. You have to understand it at first, than you can help your team become effective more quickly. Authors of this study work as team coaches in Team Academy Debrecen. In the last 6 years we have worked with several teams and experienced how group dynamics present at the teams and change through the learning process. We have faced with great storming period at different teams and managed to build high performing entrepreneur teams as well. Our experiences are introduced as case studies, after analysing, consequences will be concluded. As in the EFQM model we can find that to survive in the global competitive markets companies need the best teams for the best results.